EFFECT OF DIETARY SUPPLEMENTATION WITH ASTAXANTHIN ON THE HEMATOLOGICAL AND BIOCHEMICAL RESPONSE OF NILE TILAPIA (Oreochromis niloticus) - ARACATI, M. F.; OLIVEIRA, S. L.; RODRIGUES, L. F.; COSTA, C. C.; CONDE, G.; CAVALLI, B. J.; SILVA, H. C. P.; IBELLI, B. C. C.; SCARABEL, V. L.; SILVA, I. C.; BELO, M. A. A. (Ars Veterinaria, 2021)
This study aimed to evaluate the effect of astaxanthin on the hematological, biochemical and somatic response of Nile tilapia (Oreochromis niloticus) orally administered in the feed for a period of 60 days. For the study, 105 tilapia (n=35) from the same spawn were used, constituting the following treatments: Control = animals (not treated with astaxanthin); T100 and T200 = fish treated with 100 and 200 mg of astaxanthin/kg of feed, respectively. There were no hematological alterations in red blood cells counts, hematocrit, hemoglobin, MCV and MCHC. In addition, astaxanthin-fed tilapia presented a better thrombocyte and leukocyte responses with a marked decrease in the number of thrombocytes, lymphocytes and neutrophils. Among treatments, there were no changes in serum levels of total protein, albumin, globulins, aspartate aminotransferase and alkaline phosphate. Treatment with astaxanthin resulted in a decrease in triglyceride and glucose levels, as well as increase in hepatosomatic indices. The results of hematological and biochemical analyzes of tilapias demonstrated the clinical safety of this carotenoid, not causing harmful effects to the health of fish. Therefore, the antioxidant activity of this compound in tilapias resulted in an improvement in the leukocyte profile and contributed to hypolipidemic effects at the dose of 200mg of astaxanthin/kg of feed.